Nano "Koosh Balls" of Mesoporous MnO2: Improved Supercapacitor Performance through Superior Ion Transport. Issue 17 (23rd February 2017) - Maqbool, Qysar; Singh, Chanderpratap; Jash, Priyajit; Paul, Amit; Srivastava, Aasheesh
Abstract: Manganese dioxide nanomaterials with "Koosh‐ball"‐like morphology (MnO2 ‐KBs ) as well as worm‐like nanotubes (MnO2 ‐NWs ) are obtained by employing Tween 20 as the reducing and structure‐directing agent, and KMnO4 as a MnO2 precursor. Whereas theMnO2 ‐KBs are interconnected through tubular extensions, theMnO2 ‐NWs are largely disconnected. BothMnO2 ‐KBs andMnO2 ‐NWs have large BET surface areas (>200 m 2 g −1 ), and are thermally robust up to 300 °C. Electrochemical studies reveal that the highest specific capacitance ( C sp ) obtained forMnO2 ‐KBs (272 F g −1 ) is significantly higher than that ofMnO2 ‐NWs (129 F g −1 ). The C sp values correlate well with the electroactive surface areas of the materials:MnO2 ‐KBs have a significantly higher electrolyte‐accessible surface area. Electrochemical impedance spectroscopy (EIS) reveals a higher electron‐transfer rate at the electrode/electrolyte interface forMnO2 ‐KBs than forMnO2 ‐NWs . The multiple tubular interconnections between individualMnO2 ‐KBs allow improved ion penetration and act as conduits for their propagation, shortening the diffusion distances of the ions from external electrolytes to the interior of the MnO2 framework. Thus, this work exemplifies the importance of interconnections for enhancing the electrochemical performance of nanomaterials employed for energy storage. Abstract : Connections help : Interconnected "Koosh ball" morphology in MnO2 nanomaterials offers enhanced charge storage and propagation, resulting in improved supercapacitor performance (see figure).